Association between preoperative serum albumin level and postoperative wound complications in emergency laparotomy - Pant, Sudip; Aryal, Rishi Kant; Thapa, Nirmal (Journal of Karnali Academy of Health Sciences, 2026)
Introduction: Serum albumin level is a standard, readily available parameter that predicts preoperative mortality and morbidity. Levels above 3.5 g/dL indicate sufficient protein reserves to support biological processes. Patients with levels below 3.2 g/dL are more likely to have poor outcomes. Methods: This was a cross-sectional study from April to October 2023 at Bir Hospital’s Department of General Surgery, using convenience sampling of patients undergoing emergency laparotomy. Eligible participants were adults 20+ who consented. Exclusions included icterus, hemoglobin <7 g/dL, recent transfusion or trauma, diabetes, chronic renal or liver disease, or steroid use. Participants had standardized closure, were monitored daily for postoperative complications, including SSI (per CDC definitions), and were followed for up to 1 month. Data were analyzed in SPSS (mean ± SD for continuous, frequencies/ percentages for categorical, Chi-square test, p<0.05). Results: Our study involved 95 patients, 31% female and 69% male, aged 20 to 82. Forty percent had hypoalbuminemia (serum albumin <3.2 gm/dL). Postoperative wound complications occurred in 36.8% (n=35). Surgical Site Infection was seen in 10 patients with albumin >3.2 g/dL and 19 with <3.2 g/dL (p < 0.001). Wound dehiscence occurred in 6 cases with albumin <3.2 (p < 0.002). Lower albumin levels significantly increase the risk of complications (p < 0.001). Conclusion: Our study showed that serum albumin < 3.2 g/dL was associated with higher rates of wound complications, notably Surgical Site Infection. Preoperative serum albumin testing is cost-effective, predicts postoperative risks, and aids surgeons in nutritional decisions.